Práticas de leitura na cibercultura e a formação do leitor crítico : fandom e transmidialidade na série Percy Jackson e os olimpianos - Koziel, Elenice (2015)
The contemporary reader has many technological resources that allow him to give a substantive response to reading. His skills for analysis and perception also involve understanding of other artistic-media content that converge in cyberspace. It is in the fandom - virtual communities of fans - that these responses appear more intense and creative way. Some of the creative responses of readers/fans - fanfictions, fan arts, fan films - as well as the critical answers posted as comments on virtual platforms which we have studied in this research. Thus, we reflect on the practices of reading among young people today, focusing on the fandom of Percy Jackson and the Olympians, by Rick Riordan, and we discuss the role of schools and the agents involved in readers education, especially readers of literary texts in cybercultural context. Researchers who study the socio-cultural changes resulting from the interaction of society with digital media, such as Pierre Lévy, Henry Jenkins and Brazilian André Lemos and Lucia Santaella are the major sources used throughout this research. When analyzing the performance of readers/fans in cyberspace, we find that the fandom becomes a reading mediation space one it provides interaction between the fans, creativity and critical thinking through the virtual environment, contributing to the formation critical readers.